Management of Social Media Instagram @humas.lldikti3 in Strengthening the Function of Government Public Relations - Sojapani, Istiqfarha; Patrianti, Tria (Fakultas Ushuluddin, Adab dan Dakwah, Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2024)
Submission of verified government information must be provided by the Region III Higher Education Service Institution, as the government institution that oversees universities in the Jakarta area. This requires strengthening the public relations function because the use of social media is not yet optimal in each tertiary institution in LLDikti Region III. This research aims to determine the management of LLDikti Region III Instagram social media in strengthening the function of government public relations. This research uses a qualitative descriptive method, with data collection techniques in the form of interviews and documentation. The theories used in this research are the Social Media Management Theory by Chris Heuer and the Government Public Relations Function Theory by Rusady Ruslan. The research results show that the social media management carried out has provisions and policies for packaging, disseminating and responding to messages, as well as collaborating with stakeholders. Apart from that, LLDikti Region III safeguards government policies of the Ministry of Education and Culture, provides information services based on the KIP Law, and acts as a proactive mediator in bridging the interests of the institution with the public, as well as creating political security stability in each uploaded content.